Green Accounting And Material Flow Cost Accounting (MFCA) For The Sustainable Development Of Palm Oil Companies In Indonesia - Mega Arisia Dewi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The MFCA concept is anticipated to introduce a new approach in supporting the achievement of the SDGs, particularly in the environmental sector. This study aims to explore the impact of implementing green accounting and material flow cost accounting on the sustainable development of oil palm plantation companies in Indonesia. The data analysis method employed is multiple linear regression. The findings indicate that both green accounting and material flow cost accounting (MFCA) have a positive and significant influence on the sustainable development of palm oil plantation companies in Indonesia. Companies that incorporate green accounting into their financial reporting not only gain public trust but also enhance their ability to operate sustainably. This highlights that aligning corporate growth with environmental stewardship can significantly contribute to long-term business sustainability. Consequently, stakeholders should advocate for companies to prioritize environmental protection and social responsibility alongside profitability.